COVID-19 and Internationalization in the MENA Region - Marchesini, Giulia (International Higher Education, 2020)
In the Middle East and North Africa, both higher education and internationalization face challenges. Young people experience high levels of exclusion and unemployment. The attractiveness of the region is limited. A World Bank/Center for Mediterranean Integration (CMI) report analyzes the status of internationalization in the region today. It suggests that, in the COVID-19 context, internationalization at home represents a key starting point for MENA to catch up on the internationalization agenda.